\require{AMSmath}

Nog een paar voorbeelden...

$
\eqalign{
  & f(x) =  - \frac{1}
{{3x^{2} }} =  - \frac{1}
{3}x^{ - 2}  \to f'(x) =  - \frac{1}
{3} \cdot  - 2 \cdot x^{ - 3}  = \frac{2}
{{3x^{3} }}  \cr
  & g(x) = 2 - \frac{1}
{{\left( {3x} \right)^{3} }} = 2 - \left( {3x} \right)^{ - 3}  \to g'(x) =  -  - 3 \cdot \left( {3x} \right)^{ - 4}  \cdot 3 = \frac{9}
{{\left( {3x} \right)^{4} }}  \cr
  & of\,\,beter:  \cr
  & g(x) = 2 - \frac{1}
{{\left( {3x} \right)^{3} }} = 2 - \frac{1}
{{27}}x^{ - 3}  \to g'(x) =  - \frac{1}
{{27}} \cdot  - 3x^{ - 4}  = \frac{1}
{{9x^4 }} \cr}
$

En nog zo iets....

$
\eqalign{
  & y = \frac{{x^{2} }}
{{\root 3 \of x }} = \frac{{x^{2}}}
{{x^{\frac{1}
{3}} }} = x^{2} \cdot x^{ - \frac{1}
{3}}  = x^{1\frac{2}
{3}}  = x^{\frac{5}
{3}}   \cr
  & y' = \frac{5}
{3}x^{\frac{2}
{3}}  = \frac{5}
{3}\root 3 \of {x^{2}}  \cr}
$


©2004-2022 WisFaq